96.3k views
2 votes
Using two or more complete sentences, describe and correct the error in the solution.

Solve the system of equations.

3x - 2y = 2

9x - 6y = 6

3x - 2y = 2 → 9x - 2y = 6
9x - 6y = 6 → 9x - 6y = 6
-8y = 12
y = 1.5
3x - 2y = 2 → 3x - 2(1.5) = 6
3x - 3 = 6
3x = 9
x = 3​

User AKHolland
by
5.3k points

1 Answer

3 votes

Answer:

In the very first step, when they multiply both sides by 3 the -2y should become -6y but instead it stays as -2y. The correct solution would be:

9x - 6y =6

9x - 6y = 6

0 = 0

This means there are infinite solutions.

User Doug Couvillion
by
5.8k points